The chimpanzees of happytown - Andreae, Giles; Parker-Rees, Guy (Orchard London, 2009)
Life is no fun for the chimps in Drabsville - the mayor demands that all their houses look the same and that no one should have a good time. But things take a more colourful turn when Chutney arrives, carrying a tiny seed box